Die G7/G8-Gipfel in der internationalen politischen Ökonomie: Das Beispiel Währungs- und Finanzpolitik - Schoppengerd, Stefan (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 2007)
The G7 was established as a reaction to the economical and political crises of the mid-nineteen seventies. Its further development towards a complex G7/G8-system becomes especially apparent in the example of politics of currencies and finance. The group’s possibilities to act effectively are increasingly proving to be limited; furthermore the group is not able to react adequately to criticism and protests coming from various social movements.